Improving biogas production with application of trimetallic nanoparticle using response surface methods - Jadhav, Pramod; Krishnan, Santhana; Patil, Reshma Rohit; Bhuyar, Prakash; Zularisam, Abdul Wahid; Narayanamurthy, Vigneswaran; Mohd Nasrullah, Zulkifli (Elsevier, 2024)
The potential of trimetallic nanoparticles (TMNPs) to enhance biogas production through microbe-to-microbe interactions and boost biogas yield is evident. This present study employed the central composite design (CCD) of response surface methods (RSM) to determine the optimal conditions of iron-cobalt-zinc TMNPs influenced anaerobic digestion for higher biogas yield. The impact of initial pH (6.6–7.4), TMNPs concentration (0–30 mg L−1), temperature (25-45 °C), and hydraulic retention time (HRT) (0-4 days) were modelled for improved biogas production. The results indicated that the linear model terms of pH and TMNPs concentration, and quadratic model terms of temperature and HRT, significantly affect the biogas production. Linear model terms of TMNPs, temperature, pH, and HRT have significant interactive effects and the numerical analysis identified the best conditions for the evaluated parameters. Ideal anaerobic process settings generated a maximum cumulative biogas production of 3700 mL−1POME than blank (2000 mL−1), corresponding to an 85 % yield. Optimizing the initial pH, TMNPs concentration, temperature, and HRT can significantly improve biogas yield and could be helpful for developing more efficient AD processes at large volume and commercial biogas plants. Promoting TMNPs as catalysts positively improves an AD process towards sustainable biogas production.